Penerapan Perkalian Matriks dan Invers dalam Algoritma Hill Cipher untuk Pengamanan Pesan Teks - Refelita Sari Banjarnahor; Nataniel Buala Theos Gulo; Nia Rahmadani; Nikolas Gultom; Parulian Pardede (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The rapid development of digital communication technology has increased the need for effective and reliable data security systems. One classical cryptographic method that remains relevant for study is the Hill Cipher, which utilizes linear algebra concepts such as matrix multiplication and matrix inversion in the encryption and decryption processes. This study aims to implement these operations in securing text messages and to evaluate their security level. The research method used is descriptive analytical through literature review and manual calculation simulations of the Hill Cipher algorithm. The results show that the encryption process is performed by multiplying a key matrix with a plaintext vector in modular arithmetic, while the decryption process uses the inverse of the key matrix (Siahaan & Siahaan, 2018; Sujarwo, 2024). This approach allows encryption to be performed in blocks, thereby increasing complexity and reducing easily analyzable patterns compared to classical substitution methods (Acharya et al., 2009). However, the Hill Cipher has a fundamental weakness: it is vulnerable to unknown-plaintext attacks because the key matrix can be reconstructed if enough plaintext-ciphertext pairs are available (Jain & Arya, 2022). Furthermore, successful decryption heavily depends on the existence of the matrix inverse in a given modulus. Therefore, although the Hill Cipher is no longer suitable for modern security systems, this algorithm remains valuable as a learning medium for understanding the application of matrix concepts and modular arithmetic in cryptography. The implication of this research is that integrating mathematical concepts into cryptography can enhance students' conceptual understanding of linear algebra applications in the field of information technology.